Traditional Leadership Succession and Appointment Processes in Zimbabwe: the case of Masvingo Province. - Gumbi, Nomore (2017)
The institution of Traditional Leadership is as old as history and it has been part and parcel of governance processes since time immemorial. The issues of succession and appointment werebeing handled by spiritual mediums following the different systems pertaining to each culture and tribe during the pre-colonial era. With the coming of post independence Zimbabwe the succession and appointment processes of traditional leaders raised a lot of questions and connotation because of political involvements in the selection and appointment of traditional leaders. The conflicts which has emanated from the succession and appointment of traditional leaders have resulted in chaos and at the end it have attracted many scholars and students to dig deep investigating the subject matter. There are also irregularities in the nomination processes used in different tribes which have made it difficult to come up with policies to reduce these conflicts.